Outside the Lines : How Embracing Queerness Will Transform Your Faith - Kim-Kort, Mihee (Book collections on Project MUSE., 2018)
Mihee Kim-Kort is a wife, a mom, and a Presbyterian minister. And she's queer. As she became aware of her queer sexuality, Mihee wondered what that meant for her spirituality. But instead of pushing her away from God, her queerness has brought her closer to Jesus and taught her how to love better. In Outside the Lines, Mihee shows us how God, in Jesus, is oriented toward us in a queer and radical way. Through the life, work, and witness of Jesus, we see a God who loves us with a queer love. And our faith in that God becomes a queer spirituality--a spirituality that crashes through definitions and moves us outside of the categories of our making. Whenever we love ourselves and our neighbors with the boundary-breaking love of God, we live out this queer spirituality in the world. With a captivating mix of personal story and biblical analysis, Outside the Lines shows us how each of our bodies fits into the body of Christ. Outside the lines and without exceptions.